(-5) elevado a 2 - 4 elevado a 2 / 2 elevado a -1 + 2 elevado a -2
Soluções para a tarefa
Respondido por
0
Resposta:
12
Explicação passo-a-passo:
.. (- 5)² - 4² / 2^-1 + 2^-2 = 25 - 16 / (1/2)¹ + (1/2)²
.. = 9 / (1/2 + 1/4)
.. = 9 / (2/4 + 1/4)
.. = 9 / (3/4)
.. = 9 . 4 / 3
.. = 3 . 4
.. = 12
Respondido por
0
(-5) elevado a 2 - 4 elevado a 2 / 2 elevado a -1 + 2 elevado a -2 :
(-5)^2-4^2/2^-1+2^(-2)=
=(25)-(2^4)/(2^-1)+2^(-2)
=25-(2^4+1)+2^(-2)
=25-(2^5)+2^(-2)
=25-(32)+1/4
=24-32+1/4
=-8+1/4
=-8+0,25
=-7,75
=-775/100
=-775÷5/100÷5
=-155/20
=-155÷5/20÷5
=-31/4
espero ter ajudado!
bom dia !
Perguntas interessantes
Matemática,
11 meses atrás
Matemática,
11 meses atrás
Português,
11 meses atrás
Matemática,
1 ano atrás
Ed. Moral,
1 ano atrás
Geografia,
1 ano atrás
Biologia,
1 ano atrás
Física,
1 ano atrás